Miniature single-mode fiber refractive index interferometer sensor based on high order cladding mode and core-offset - Wong, Wei Chang (2013)
A miniature single-mode fiber (SMF) refractive index (RI) interferometer sensor based on high order cladding mode and core offset is presented. The sensor is fabricated by first splicing a very short SMF to another SMF with core-offset to induce cladding mode propagation along the short SMF. The end of the SMF will be melted into a rounded tip to excite the propagating cladding mode into higher order at reflection which creates large phase delay. High RI sensitivity of 1.24 × 10-4 refractive index unit (RIU) and 8.35 × 10-5 RIU for RIU of 1.3350 and 1.3845, are obtained, respectively, for the physical length of 690- μm sensor.